Macroeconomic success and social vulnerability : lessons for Latin America from the Celtic Tiger - Kirby, Peadar (ECLAC SantiagoCL, 2003)
Examines the period of high economic growth in Ireland known as the Celtic Tiger which lasted from 1995 until 2000. Identifies the links between the nature of the Irish model and its social impact, especially features that can be grouped under the concept of 'social vulnerability'. Forms the basis for drawing some policy lessons for Latin America.